Lysophosphatidic Acid Activates Nuclear Factor Kappa B and Induces Proinflammatory Gene Expression in Endothelial Cells - Palmetshofer, Alois; Robson, Simon C.; Nehls, Volker (Thrombosis and Haemostasis, 1999)
The cellular phospholipid, lysophosphatidic acid (LPA), released by activated platelets and fibroblasts or, at high levels, from ovarian and cervical carcinomas is a powerful serum mitogen that may modulate several signaling pathways in endothelial cells (EC). Hence, LPA could function in a paracrine manner during EC-platelet interactions at sites of vascular injury.Here, we demonstrate activation of the transcription factor nuclear factor kappa B (NF-κB) in EC following exposure to LPA. EC activation was further characterized by increased levels of mRNA transcripts encoding E-selectin, Intercellular Adhesion Molecule-1, Interleukin-8 and Monocyte Chemoattractant Protein-1. These effects were inhibited by preincubating EC either in the presence of mepacrine (to block phospholipase A2) or of pertussis toxin (to increase ADP-ribosylation of Gi proteins). No inhibition was observed in the presence of putative LPA receptor antagonists suramin or thrombospondin.LPA induces a proinflammatory activation of endothelial cells that (i) involves Gi proteins; (ii) depends on phospholipase A2 activity; (iii) is associated with the activation of NF-κB and (iv) results in increased expression of proinflammatory genes. We propose that LPA release by activated platelets may directly modulate vascular inflammatory responses.Abbreviations: EC, endothelial cells; LPA, lysophosphatidic acid; NF-κB, nuclear factor kappa B; PA, phosphatidic acid; IL-8, interleukin-8; MCP-1, monocyte chemoattractant protein-1, ICAM-1, intercellular adhesion molecule-1, vascular adhesion molecule-1; GAPDH, glycerol aldehyde phosphate dehydrogenase; MAPK, mitogen activated kinase, MEK, MAPK kinase, PAEC, porcine aortic EC.
Keywords: Lysophosphatidic acid; nuclear factor kappa B; transcription factor; inflammation; endothelial cells; platelets; gene expression